Changing patterns of polish labour migration after the UK's opening of the labour market? Insights from rural case-studies in the opolskie and Świetokrzyskie voivodship - Elrick, Tim; Brinkmeier, Emilia (Polish Migration to the UK in the 'New' European Union: After 2004, 2009)

Der Dönerkebap als Integrationschance? Struktur und Wirtschaftsverflechtungen im ‘türkischen’ Gastgewerbe in Nürnberg. Eine Studie am Beispiel von Dönerkebap-Verkaufsstellen - Fallenbacher, Tim (2001)

Der Einfluss von Migration auf die Herkunftsgemeinden. Fallstudien polnisch-deutscher Migrationen - Lewandowska, Emilia; Elrick, Tim (Von Polen nach Deutschland und zurück. Die Arbeitsmigration und ihre Herausforderungen für Europa, 2007)

Diffusionsforschung - Elrick, Tim (Methoden-Lexikon für die Sozialwissenschaften, 2014)

‘Ethnic Business’ in Nürnberg. Fallstudie Dönerkebap - Fallenbacher, Tim (Mitteilungen der Fränkischen Geographischen Gesellschaft, 2001)

Everts, Jonathan 2008: Konsum und Multikulturalität im Stadtteil. Eine sozialgeographische Analyse migrantengeführter Lebensmittelgeschäfte. transcript Verlag: Bielefeld. - Elrick, Tim (2015)

Gravitationsmodell - Elrick, Tim (Methoden-Lexikon für die Sozialwissenschaften, 2014)

Kartenvergleich zum Aufspüren gesellschaftlicher Gemachtheit von Karten: Eine Innenstadt - verschiedene Karten. - Elrick, Tim; Glasze, Georg (Diercke. Reflexive Kartenarbeit. Methoden und Aufgaben., 2016)

Kolb, Holger und Henrik Egbert (eds.) 2008: Migrants and Markets. Perspectives from Economics and the Other Social Sciences. Amsterdam University Press: Amsterdam. - Elrick, Tim (2009)

Matching and making labour demand and supply: Agents in polish migrant networks of domestic elderly care in Germany and Italy - Elrick, Tim; Lewandowska, Emilia (Journal of Ethnic and Migration Studies, 2008)
This paper explores the role of agents in migrant networks in the domestic elderly care sector. It is based on a study of female migrants from Poland who work in the sector in Germany and Italy. Using evidence gathered from qualitative interviews, we illustrate the importance of ties other than friends, families and communities in the migration process, including actors such as employers and recruitment agents. We also show that agents - in contrast to intermediaries - are significant actors in migrant networks and can be regarded as perpetuators of migration within these networks. Furthermore, we conclude that the role of agents in migrant networks has been underestimated. Rather than simply helping to match labour supply with labour demand, agents appear to offer migrants social and emotional support as well.
Keywords: migration networks; Polish migration; migration industry

Migration networks and policy impacts: Insights from Romanian-Spanish migrations - Elrick, Tim; Ciobanu, Oana (Global Networks - A Journal of Transnational Affairs, 2009)
Migration networks are now generally recognized as a means of adapting to or circumventing states' migration policies, but little research has been carried out on quite how they work. In this article, we analyse migrant networks between Romanian and Spain over the last 20 years. We contrast two villages to reveal how different reactions to policy changes depend on the level of development of migration networks. Among these policy changes are regularizations of irregular migrants in Spain, the visa-free entry of Romanians into Schengen countries enacted in 2002, EU enlargements in 2004 and 2007, and a bilateral agreement on labour recruitment between Romania and Spain. We conclude that networks can help migrants circumvent restrictive policies, foster the effective take-up of permissive policies or even impede them, depending on the development of the migration networks of the communities.
Keywords: migration networks; migration theory; Romanian migration; labour migration; migration industry

Modifiable Area Unit Problem - Elrick, Tim (Methoden-Lexikon für die Sozialwissenschaften, 2014)

Netzwerke und ihr Einfluss auf Migrationspolitik. Schlussfolgerungen aus dem rumänisch-spanischen Migrationsraum - Elrick, Tim (focus Migration Kurzdossiers, 2008)

Politici de migratie si strategii ale migrantilor transnationali între România si Spania - Elrick, Tim; Ciobanu, Ruxanda Oana (Sociologia Migratiei: Teorii si studii de caz romanesti., 2009)

Raumwissenschaftlich-quantitive Ansätze in der Geographie - Elrick, Tim (Methoden-Lexikon für die Sozialwissenschaften, 2014)

Renzension von: Everts, Jonathan 2008: Konsum und Multikulturalität im Stadtteil. Eine sozialgeographische Analyse migrantengeführter Lebensmittelgeschäfte. transcript Verlag: Bielefeld. - Elrick, Tim (2015)

Rezension von: Goeke, Pascal 2007: Transnationale Migrationen - Elrick, Tim (2008)

Rezension von: Kolb, Holger und Henrik Egbert (eds.) 2008: Migrants and Markets. Perspectives from Economics and the Other Social Sciences. Amsterdam University Press: Amsterdam. - Elrick, Tim (2009)

Shift-Share-Analyse - Elrick, Tim (Methoden-Lexikon für die Sozialwissenschaften, 2014)

Sozialwissenschaftliche tag-Analyse mit OpenStreetMap-Daten am Beispiel religiöser Andachtsstätten in Deutschland. - Elrick, Tim (Kartographische Nachrichten, 2014)
Das Aufkommen von Web 2.0-Technologien auch im kartographischen Bereich eröffnet die Möglichkeit, soziale Phänomene vielfältiger als in amtlichen Karten zu repräsentieren. Dieser Beitrag führt am Beispiel der Open-StreetMap-Datenbank eine sozialwissenschaftliche Analyse kartographischer Repräsentationen religiöser Andachtsstätten in Deutschland im Hinblick auf diese Vielstimmigkeit durch und zeigt dabei die methodischen Möglichkeiten und Beschränkungen einer Attribut-Analyse von crowdsourced Geodaten auf.   The emergence of cartographic web 2.0 technologies opens the floor for a potentially more multifarious representation of social phenomena than in official maps. This paper examines cartographic representations of places of worship in Germany taking a sample from the OpenstreetMap database to analyze the polyphony in the data. It is followed by a methodological discussion of the applied tag analysis of the crowdsourced geodata.
Keywords: OpenStreetMap; Kritische Geoweb-Forschung; Places of worship

Standortquotient - Elrick, Tim (Methoden-Lexikon für die Sozialwissenschaften, 2014)

The influence of migration on origin communities: Insights from polish migrations to the West - Elrick, Tim (Europe-Asia Studies, 2008)
This article sheds light on the impact of migration on origin communities by focusing on two case studies in different regions in Poland. Besides the economic consequences, the social and cultural consequences of migration for community cohesion and the lives of its members are highlighted, with reference to an emerging culture of migration in the communities. By presenting different migration patterns prevalent before and after Poland's accession to the European Union, the article demonstrates the important differences caused by 'visible migration' and 'hidden migration' in the communities of origin, taking into account especially the temporal dimension.
Keywords: migration networks; culture of migration; Polish migration

The new face of East-West migration in Europe - Elrick, Tim; Favell, Adrian (Taylor & Francis, 2008)

Transnational migration networks of Eastern European labour migrants - Elrick, Tim (2009)

Vielfalt durch Zuwanderung. Stadtkultur - Elrick, Tim (Der Nürnberg-Atlas. Vielfalt und Wandel der Stadt im Kartenbild, 2007)

Walking Interview - Elrick, Tim (Methoden-Lexikon für die Sozialwissenschaften, 2014)

Zeitgeographie - Elrick, Tim (Methoden-Lexikon für die Sozialwissenschaften, 2014)